Song structure and syllable and song repertoires of the Saffron Finch (Sicalis flaveola pelzelni) breeding in Argentinean pampas - Benitez Saldivar, Maria Juliana (2018)
Empirical descriptions of vocal behaviour in avian communication are important in understanding its meaning and role in shaping the social and genetic relationships among individuals in a population. In this study, we provide the first detailed analysis of the vocal behaviour of the Saffron Finch (Sicalis flaveola pelzelni), a neotropical songbird found in rural and semi-open areas of Argentina that is frequently captured for the pet trade. We identify syllables, quantify the fine structural characteristics of the song, and describe the size and structure of the song repertoire. Further, we use networks to explore whether this species uses syntactical rules for creating their songs. Our analyses reveal that Saffron Finch males have a large syllable repertoire. Song repertoire size is not fixed, and birds recombine their syllables to produce highly variable songs. In addition, they sing with immediate variety, seldom repeating a song before switching to a new song and song sharing was very limited among our sampled individuals.